The effects of an 8-week knitting program on osteoarthritis symptoms in elderly women: A pilot randomized controlled trial. (July 2021) - Leonard, Guillaume; Paquet, Nicole; Guitard, Paulette; Toupin-April, Karine; Cavallo, Sabrina; Paterson, Gail; Aydin, Sibel Z.; Bakirci, Sibel; Coulombe-Lévêque, Alexia; Brosseau, Lucie
Abstract: Background: Exercise therapy is effective in reducing symptoms and disability associated with hand osteoarthritis (HOA) but often has low adherence. An intervention consisting in a meaningful occupation, such as knitting, may improve adherence to treatment. This pilot randomized controlled trial (RCT) studied the adherence and clinical effectiveness of a knitting program in older females suffering from HOA to evaluate the acceptability of this intervention and assess the feasibility of a larger-scale RCT. Methods: Single-blind, two-arm pilot RCT with a parallel group design with 37 participants (18 control, 19 intervention). Control participants were given an educational pamphlet and assigned to a waiting list. The knitting program (8-week duration) had two components: bi-weekly 20-min group knitting sessions and daily 20-min home knitting session on the 5 remaining weekdays. Measures included knitting adherence (implementation outcomes) as well as stiffness, pain, functional status, hand physical activity level, patient's global impression of change, health-related quality of life, self-efficacy, and grip strength (clinical outcomes measured throughout the 8-week program and 4 weeks after the intervention). Results: Our protocol is feasible and the intervention was acceptable and enjoyable for participants, who showed high adherence. No difference was observed between the two groups for any of the clinical outcome measures (all p > .05). Conclusion: Knitting is a safe and accessible activity for older women with HOA. However, our 8-week knitting program did not result in improvements in any of our outcome measures. Knitting for a longer period and/or with higher frequency may yield better outcomes.